Progressive multifocal leukoencephalopathy and sarcoidosis under interleukin 7: The price of healing. Issue 5 (September 2020) - Guffroy, Aurélien; Solis, Morgane; Gies, Vincent; Dieudonne, Yannick; Kuhnert, Cornelia; Lenormand, Cédric; Kremer, Laurent; Molitor, Anne; Carapito, Raphaël; Hansmann, Yves; Poindron, Vincent; Martin, Thierry; et al.
Abstract : Objective: To report the association of JC virus infection of the brain (progressive multifocal encephalopathy [PML]) during the course of sarcoidosis and the challenging balance between immune reconstitution under targeted cytokine interleukin 7 (IL7) therapy for PML and immunosuppression for sarcoidosis. Methods: Original case report including deep sequencing (whole-exome sequencing) to exclude a primary immunodeficiency (PID) and review of the literature of cases of PML and sarcoidosis. Results: We report and discuss here a challenging case of immune reconstitution with IL7 therapy for PML in sarcoidosis in a patient without evidence for underling PID or previous immunosuppressive therapy. Conclusions: New targeted therapies in immunology and infectiology open the doors of more specific and more specialized therapies for patients with immunodeficiencies, autoimmune diseases, or cancers. However, before instauration of these treatments, the risk of immune reconstitution inflammatory syndrome and potential exacerbation of an underlying disease must be considered. It is particularly true in case of autoimmune disease such as sarcoidosis or lupus.